Methicillin-Resistant Staphylococcus aureus–Associated Infections following Septorhinoplasty - Abuzeid, Waleed M.; Brandt, Michael G.; Moyer, Jeffrey S.; Baker, Shan R. (Facial Plastic Surgery, 2012)
Septorhinoplasty is associated with postoperative infection in less than 2% of cases, even without the use of prophylactic antibiotics. However, there is a concern that increasingly prevalent, highly virulent pathogens such as MRSA may predispose to postoperative infections. Over the past several decades, MRSA has emerged as the most important cause of antibiotic-resistant nosocomial infection. MRSA-associated infections related to nasal surgery are underreported in the literature. We present a case of MRSA-associated infection following a routine septorhinoplasty in a health care worker. We discuss the incidence of this complication and contributing risk factors. The classification of MRSA-associated infections into genotypically distinct hospital-acquired and community-acquired subtypes is reviewed, and the associated differences in epidemiology, clinical presentation, and antibiotic susceptibility are discussed. A comprehensive strategy incorporating diagnostic workup, preventative management based upon preoperative risk stratification, and treatment of MRSA-associated soft tissue infections is presented.
Keywords: septorhinoplasty; rhinoplasty; infection; MRSA; complications